2013
DOI: 10.1051/0004-6361/201321088
|View full text |Cite
|
Sign up to set email alerts
|

Two new SB2 binaries with main sequence B-type pulsators in theKeplerfield

Abstract: Context. OB stars are important in the chemistry and evolution of the Universe, but the sample of targets that is well understood from an asteroseismological point of view is still too limited to provide feedback on the current evolutionary models. Aims. We extend this sample with two spectroscopic binary systems. Our goal is to provide orbital solutions, fundamental parameters, and abundances from disentangled high-resolution high signal-to-noise spectra, as well as to analyse and interpret the variations in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 40 publications
(42 reference statements)
1
35
0
Order By: Relevance
“…Unfortunately, we have only two seismic values of α ov for pulsating B stars in close binaries (Table 1), but several new case studies are on the way, such as two SB2 pulsators discovered from Kepler data (Pápics et al 2013). Although the current sample is too small to be statistically meaningful, this is one of the important and promising ways towards improving the implementation of the input physics of massive stars.…”
Section: Compilation Of Seismic Analysis Results Of Ob-type Starsmentioning
confidence: 97%
“…Unfortunately, we have only two seismic values of α ov for pulsating B stars in close binaries (Table 1), but several new case studies are on the way, such as two SB2 pulsators discovered from Kepler data (Pápics et al 2013). Although the current sample is too small to be statistically meaningful, this is one of the important and promising ways towards improving the implementation of the input physics of massive stars.…”
Section: Compilation Of Seismic Analysis Results Of Ob-type Starsmentioning
confidence: 97%
“…We used the method described in Pápics et al (2013) to determine the RVs of both components from the composite observed spectra. Briefly, the method relies on the fitting of composite synthetic spectra to the observations, and comprises of two basic steps.…”
Section: Modelling the Light-and Rv-curve Datamentioning
confidence: 99%
“…The fact that the system is eccentric and the intrinsic pulsations of the more evolved component are in the range below 6 d −1 (69.4 µHz) makes it an interesting target to search for pulsations that are resonantly driven by the dynamic tide. These so-called tidally induced pulsations (Aerts et al 2010, Chapter 2) have so far been detected in BA main-sequence stars with masses below 5 M ⊙ (e.g., Welsh et al 2011;Thompson et al 2012;Hambleton et al 2013;Pápics et al 2013) but never in early B-type stars. Should this type of stellar oscillation be found in either of the stellar components of the Spica system, it will be the first massive binary in which resonantly driven oscillations have been detected.…”
Section: Introductionmentioning
confidence: 99%
“…The subject of tidal asteroseismology, i.e., stellar modelling based on tidally excited or tidally affected pulsations, only turned into a practical science since the availability of the uninterrupted CoRoT and Kepler lightcurves of either eclipsing binaries with tidally excited g-modes (e.g., Maceroni et al 2009;Welsh et al 2011;Hambleton et al 2013;Debosscher et al 2013;Borkovits et al 2014) or pulsating stars that were initially thought to be single stars but turned out to be a member of a spectroscopic binary from follow-up data (e.g., Pápics et al 2013). In all of those studies, clear evidence was found that some or all of the g-modes are tidally triggered, after iterative light curve modelling schemes in the cases where the binary and pulsational variability are of the same order of magnitude.…”
Section: Tidal Asteroseismologymentioning
confidence: 99%